Stern-wheel steamers KLONDIKE, KENO, and NASUTLIN, probably Whitehorse, Yukon Territory, approximately 1959 - Liddle, William (1959)
On verso of image: Photo by William Liddle, Seattle. The KLONDIKE was built in 1929, the KENO was built in 1922, and the NASUTLIN was built in 1912. All were built at Whitehorse, Yukon Territory, for the upper Yukon River passenger and freight service of the British Yukon Navigation Co. (pg. 401, pg. 327, and pg. 205) Funds were provided by the Canadian government in 1961 to restore three of the famous old Yukon stern-wheelers on the beach at Whitehorse as tourist attractions. These were the CASCA, KLONDIKE and WHITEHORSE. In 1961, the KENO made a farewell voyage from Whitehorse to Dawson City. At Dawson she was placed in permanent moorings as a museum. (pg. 651) Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co, 1966). To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number